The Effects of Qinggan-27 Recipe on Nonalcoholic Steatohepatitis Induced by High-fat Diet in Rats - WenJun; Erdenebat, Khaliun; Byambaa, Tserentsoo; Enkhbat, Bayarmaa; Myagmar-Ochir, Enkhtuguldur; Lkhagvadorj, Sayamaa (Central Asian Journal of Medical Sciences, 2024)
Objective: The Qinggan-27 (QG-27) recipe is a traditional Mongolian medicine believed to improve liver function during Non-alcoholic steatohepatitis (NASH). We developed fatty liver models in rats by intragastric administration of a high-fat diet (HFD) to investigate the effects of the QG-27 recipe on the NASH model through the expression of PGC-1 α and UCP-2. Methods: Wister rats were fed with specially prepared HFD to create a pathological model for 6 weeks. After successful modeling, the patient was treated with QG-27 twice daily with intragastric administration of QG-27 at 150 mg/kg, 300 mg/kg, and 600 mg/kg, respectively, for 21 days. Biochemical, histopathological, and immunohistochemical analyses were conducted to evaluate the effect of QG-27 treatment. Results: Levels of AST, ALT, LDL-C, TG, and TC were significantly decreased, and HDL-C was increased in the intermediate dose of the QG-27 group compared to the control group (p<0.05). Immunohistochemical results demonstrated that an intermediate dose of the QG-27 recipe could significantly improve liver function in rats with fatty liver by increasing PGC-1α and UCP-2 expression. Conclusion: The intermediate (300 mg/ kg) dose of the QG-27 is a good candidate to be a dietary supplement for reducing fatty liver.